Epidemiological case-control study on the etiology of bladder cancer in Turkey - (:unkn) unknown (My University, 1990)
A case-control study of 194 patients with bladder cancer and the same number of age- and sex-matched hospital controls were interviewed to estimate the role of various factors on the etiology of bladder cancer in Turkey. There was a significant difference between the case and control groups on cigarette smoking (p < 0.001), alcohol intake (p < 0.001), Turkish coffee consumption (p = 0.01), and artificial sweeteners (p < 0.05). The risks for alcohol and tobacco users increased in correlation with the duration of exposure. The risk of bladder cancer increased directly with the quantity and frequency of alcohol intake. Alcohol and coffee drinking was found to be a promoting factor when adjusted to smoking habits (p < 0.05). No statistical comparisons could be made to clarify the risks attributed by occupation and place of residence due to small figures in each group. However, in farmers, there was a significant difference between the cases and controls on the use of artificial fertilizers and insecticides (p < 0.01). People who were exposed to unspecified chemical substances were more prone to develop bladder cancer (p < 0.001). We conclude that both personal habits and exogenous carcinogens play a role in the etiology of bladder tumors.
Keywords: bladder cancer; epidemiology; etiology